2015
DOI: 10.1177/1538574415614404
|View full text |Cite
|
Sign up to set email alerts
|

A MultiCenter Pilot Randomized Controlled Trial of Remote Ischemic Preconditioning in Major Vascular Surgery

Abstract: A pilot randomized controlled trial that evaluated the effect of remote ischemic preconditioning (RIPC) on clinical outcomes following major vascular surgery was performed. Eligible patients were those scheduled to undergo open abdominal aortic aneurysm repair, endovascular aortic aneurysm repair, carotid endarterectomy, and lower limb revascularization procedures. Patients were randomized to RIPC or to control groups. The primary outcome was a composite clinical end point comprising any of cardiovascular deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
(77 reference statements)
0
29
0
Order By: Relevance
“…In astrocytes, HIF-1 also induces the expression of P450 2C11, an arachidonic acid epoxygenase, which is protective against ischemia-reperfusion injury in multiple organ systems [22], and contributes to IPC-mediated protection [22]. HIF-1 controls the glycolytic response of immune cells and profoundly alters inflammatory responses under conditions of hypoxia [23].…”
Section: Molecular Mediators Of Preconditioningmentioning
confidence: 99%
See 2 more Smart Citations
“…In astrocytes, HIF-1 also induces the expression of P450 2C11, an arachidonic acid epoxygenase, which is protective against ischemia-reperfusion injury in multiple organ systems [22], and contributes to IPC-mediated protection [22]. HIF-1 controls the glycolytic response of immune cells and profoundly alters inflammatory responses under conditions of hypoxia [23].…”
Section: Molecular Mediators Of Preconditioningmentioning
confidence: 99%
“…HIF-1 is an upstream regulator for a series of hypoxiaresponsive genes, including glucose transporter (GLUT) 1 and vascular endothelial growth factor (VEGF), and is upregulated by hypoxic preconditioning [4,22,69]. In astrocytes, HIF-1 also induces the expression of P450 2C11, an arachidonic acid epoxygenase, which is protective against ischemia-reperfusion injury in multiple organ systems [22], and contributes to IPC-mediated protection [22].…”
Section: Molecular Mediators Of Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative ease of administration, low cost, and potential wide generalizability of RIPC make the concept a particularly attractive clinical strategy for select populations of patients that are at high risk for cerebral ischemic events in the immediate (hours to days) future. This would include patients that are about to undergo major cardiac [32,33] or carotid artery [34] surgery, as well as possibly patients with subarachnoid hemorrhage that are at high risk of developing cerebral vasospasm and accompanying delayed cerebral ischemia [35,36]. The pioneering papers in the RIPC field suggest that neuroprotection is induced rapidly [30,31,37]; however, the duration of protection has not been determined [37,38].…”
Section: Remote Preconditioningmentioning
confidence: 99%
“…To date, trials assessing the effect of RIPC in vascular surgery have used either propofol anaesthesia, 4e11 or provided no information about the anaesthetic protocol. 2,3,12 However, no clinical trial has been conducted that was specifically designed to investigate the influence of an anaesthetic regimen with propofol on the effectiveness of RIPC. Consequently, the evidence from experimental studies remains the closest estimation and a recent experimental study directly designed to investigate the adverse effects of the anaesthetic regimen on RIPC demonstrated that the use of propofol reserved the protective effect of RIPC, while protective effects were observed in animal groups receiving pentobarbital or sevoflurane/remifentanil for the induction and maintenance of anaesthesia.…”
mentioning
confidence: 99%